2015
DOI: 10.1088/0953-8984/27/45/455104
|View full text |Cite
|
Sign up to set email alerts
|

Liquid B2O3up to 1700 K: x-ray diffraction and boroxol ring dissolution

Abstract: Using high energy x-ray diffraction, the structure factors of glassy and molten B2O3 were measured with high signal-to-noise, up to a temperature of T  =  1710(20) K. The observed systematic changes with T are shown to be consistent with the dissolution of hexagonal [B3O6] boroxol rings, which are abundant in the glass, whilst the high-T (>~1500 K) liquid can be more closely described as a random network structure based on [BO3] triangular building blocks. We therefore argue that diffraction data are in fact q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 73 publications
4
54
0
Order By: Relevance
“…The pyrometer temperature was also corrected for reflection losses from a CaF 2 window and lens that were in the optical path. The diffraction data reduction and definitions of the scattering functions used are given elsewhere . The measured structure factors, S ( Q ), represented as functions of Q = (4 π sin ϑ )/ λ , with 2 ϑ the scattering angle, and λ = 0.12370 Å the X‐ray wavelength, were Fourier transformed with Q max = 20 Å −1 , without modification (window) function.…”
Section: Methodsmentioning
confidence: 99%
“…The pyrometer temperature was also corrected for reflection losses from a CaF 2 window and lens that were in the optical path. The diffraction data reduction and definitions of the scattering functions used are given elsewhere . The measured structure factors, S ( Q ), represented as functions of Q = (4 π sin ϑ )/ λ , with 2 ϑ the scattering angle, and λ = 0.12370 Å the X‐ray wavelength, were Fourier transformed with Q max = 20 Å −1 , without modification (window) function.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis, particularly of the diffraction data, requires knowledge of both the melt density and composition (Alderman et al, 2015;Alderman et al, 2014;Fischer et al, 2006;Keen, 2001). Liquid mass densities were estimated from measurements (Shiraishi et al, 1978) at 1573 K and 1673 K by linear interpolation or extrapolation using ρ = 3.373 -0.00028(T -1573) in g cm -3 and K which yields densities about 1% higher than some more recent measurements (Thomas et al, 2012).…”
Section: Sample Density and Oxidation State Estimatesmentioning
confidence: 99%
“…The Fourier transforms (defined in (Alderman et al, 2015;Alderman et al, 2014)) of the diffraction data are presented in Fig. 5a and 5b in the form of D(r) and T(r).…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments performed for example at the beamlines 11-ID-C and 6-ID-D at the APS have demonstrated that high energy X-ray diffraction measurements are an extremely effective in studying the liquid and amorphous states. A range of materials have been studied including silicate [6] and aluminate liquids [7], TiO2 [8], borates [9,10] and, recently molten uranium oxide [11,12].…”
Section: High Energy X-ray Diffractionmentioning
confidence: 99%